Inter-correlation of risk factors among heart patients - Md Jahoor Alam; Abdullah Ibrahim Alnafeesah; Mohd Saeed (AIMS Press, 2020)
Cardiovascular disease is a well-known and widely studied disease. Epidemiological studies indicated that the mortality rate due to cardiovascular diseases increases every year. According to the WHO (world health organization) report, cardiovascular disease is one of the most prevalent non-communicable diseases in Saudi Arabia. Moreover, the Ministry of Health, Kingdom of Saudi Arabia, also reported that 42% of the non-communicable disease death is associated with cardiovascular disease in Saudi Arabia. Various reports suggest that heart disease is associated with several risk factors. Moreover, diabetes is one of the high-risk factors. Clinical result suggests a good association between diabetes and cardiovascular complications. In the present work, we focus on some of the important risk factors responsible for heart disease such as weight, blood pressure, age, and diabetes. A set questionnaire, which includes all the parameters associated with cardiovascular disease, was prepared. Data collected from the heart patient's records of different hospitals in Al-Qassim, Saudi Arabia. We applied statistical tools to analyze the data. Our results shows very interactive and significant pattern. We found significant inter-correlation between the different risk factors. In conclusion, the inter-correlation among different risk factors of heart disease is found. It is suggested that both pre and post-heart patients should be more concern about these risk factors. Moreover, this study can be used for further research, and, will increase people awareness regarding their healthy choice.